Mesoscale Reaction–Diffusion Phenomena Governing Lignin‐First Biomass Fractionation. Issue 17 (8th May 2020) - Thornburg, Nicholas E.; Pecha, M. Brennan; Brandner, David G.; Reed, Michelle L.; Vermaas, Josh V.; Michener, William E.; Katahira, Rui; Vinzant, Todd B.; Foust, Thomas D.; Donohoe, Bryon S.; Román‐Leshkov, Yuriy; Ciesielski, Peter N.; et al.
Abstract: Lignin solvolysis from the plant cell wall is the critical first step in lignin depolymerization processes involving whole biomass feedstocks. However, little is known about the coupled reaction kinetics and transport phenomena that govern the effective rates of lignin extraction. Here, we report a validated simulation framework that determines intrinsic, transport‐independent kinetic parameters for the solvolysis of lignin, hemicellulose, and cellulose upon incorporation of feedstock characteristics for the methanol‐based extraction of poplar as an example fractionation process. Lignin fragment diffusion is predicted to compete on the same time and length scales as reactions of lignin within cell walls and longitudinal pores of typical milled particle sizes, and mass transfer resistances are predicted to dominate the solvolysis of poplar particles that exceed approximately 2 mm in length. Beyond the approximately 2 mm threshold, effectiveness factors are predicted to be below 0.25, which implies that pore diffusion resistances may attenuate observable kinetic rate measurements by at least 75 % in such cases. Thus, researchers are recommended to conduct kinetic evaluations of lignin‐first catalysts using biomass particles smaller than approximately 0.2 mm in length to avoid feedstock‐specific mass transfer limitations in lignin conversion studies. Overall, this work highlights opportunities to improve lignin solvolysis by genetic engineering and provides actionable kinetic information to guide the design and scale‐up of emerging biorefinery strategies. Abstract : Consequences of confinement : Biomass conversion is central to the production of important chemicals and fuels from lignocellulose. A feedstock‐centric mesoscale modeling framework is designed to inform lignin‐first and related condensed‐phase fractionation strategies by decoupling underlying chemical reaction kinetics from mass and heat transport effects, which elucidates the consequences of biomass pore and particle size on observable laboratory measurements.